2023
DOI: 10.4103/2045-9912.345171
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen exerts neuroprotective effects by inhibiting oxidative stress in experimental diabetic peripheral neuropathy rats

Abstract: Diabetic peripheral neuropathy (DPN) is a complex disorder caused by long-standing diabetes. Oxidative stress was considered the critical creed in this DPN pathophysiology. Hydrogen has antioxidative effects on diabetes mellitus and related complications. However, there is still no concern on the beneficial effects of hydrogen in DPN. This paper aimed to evaluate the effects of exogenous hydrogen to reduce the severity of DPN in streptozotocin-induced diabetic rats. Compared with hydrogen-rich saline treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Oxidative stress damages the peripheral nervous system, such as Schwann cells, myelinated axons, and sensory neurons, among others (Chandrasekaran et al 2019 ; Fernyhough 2015 ). ROS can lead to oxidative damage in dorsal root ganglion neurons and is considered a major mechanism in the pathogenesis of DPN (Han et al 2023 ). Insufficient mitochondrial energy production can lose the ability to transport axons, further contributing to axonal injury (Rumora et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress damages the peripheral nervous system, such as Schwann cells, myelinated axons, and sensory neurons, among others (Chandrasekaran et al 2019 ; Fernyhough 2015 ). ROS can lead to oxidative damage in dorsal root ganglion neurons and is considered a major mechanism in the pathogenesis of DPN (Han et al 2023 ). Insufficient mitochondrial energy production can lose the ability to transport axons, further contributing to axonal injury (Rumora et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that H 2 could increase antioxidant enzymes, including SOD, CAT, Gpx, heme oxygenase-1 (HO-1), and NAD(P)H quinone dehydrogenase 1 (NQO1) (Liu et al, 2016;Li et al, 2019). The activation of Nrf2-mediated antioxidant signaling pathway by H 2 may be responsible for the increased expression of the antioxidant enzymes (Li et al, 2019;Zheng et al, 2021;Han et al, 2023). In conclusion, available evidence indicates the inhibitory effect of H 2 on mtROS, which may be mediated by directly scavenging free radicals, inhibiting free radical production or enhancing cellular antioxidant capacity, although the detailed mechanism needs to be further investigated.…”
Section: Reducing Mtrosmentioning
confidence: 99%
“…The protective effects of H 2 against the diabetic complications, including peripheral neuropathy [25][26][27][28][29], retinopathy [30,31], cardiomyopathy [32,33], wound healing [34][35][36], bone loss [37], and erectile dysfunction [38], have been extensively reported. STZ-induced mice or rats models were used in the above in vivo studies for diabetic complications.…”
Section: Protective Effects Of H 2 Against Metabolic Diseases 21 Diab...mentioning
confidence: 99%
“…In addition to conventional hydrogen delivery routes, some novel administration methods, such as photo-driven nanoreactor, microneedle patch, and algae-bacteria gel patch, were used, which allowed in situ continuous hydrogen production to treat chronic diabetic wounds. The inhibition of oxidative stress, inflammation, endoplasmic reticulum stress, apoptosis, and pyroptosis, as well as parthanatos (a particular type of programmed cell death that is different from the common apoptosis, necrosis, and autophagy) and activation of the mitochondrial ATP-sensitive potassium (Mito-K-ATP) pathway may be involved in the protective effects of H 2 on diabetic complications [25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Protective Effects Of H 2 Against Metabolic Diseases 21 Diab...mentioning
confidence: 99%
See 1 more Smart Citation